Islamic Educational Leadership In A Global And Multicultural Context: Challenges And Opportunities - Suyoko; Abdul Aziz (proceedings.icesy, 2026)
Islamic education in the global and multicultural era faces major challenges in maintaining the values ​​of Islamic teachings while adapting to global developments and the multicultural era. This study aims to examine the leadership of Islamic education at MTs Sunan Kalijaga Sendang, a private madrasah located in a rural area with a heterogeneous community. The main focus of the study is how the leadership at MTs Sunan Kalijaga Sendang manages challenges and finds opportunities for Islamic education leadership in the era of globalization and multiculturalism in an effort to improve the quality of education with limited resources. This study uses a qualitative method with a case study approach, where data are collected through in-depth interviews, participant observation, and document analysis. Data analysis uses the content analysis method (Miles & Huberman). The results of the study indicate that the leadership of the madrasah principal successfully applies various effective leadership styles, including transformational, collaborative, visionary, value-based, adaptive, and hastabrata leadership. Despite facing challenges in integrating Islamic noble values ​​into the global curriculum, the challenges of technology and digitalization, multiculturalism and pluralism, limited resource management and competition with other madrasas and schools, the madrasah principal succeeded in creating an inclusive and adaptive educational environment while maintaining fundamental Islamic values. Researchers also found 5 leadership opportunities, namely increasing access to technology-based education, character education in a multicultural context, a strategic role in the formation of Islamic leadership, partnerships with other educational institutions, and character building through religious education and entrepreneurship. Overall, it can be concluded that effective leadership can be a key factor in improving the quality of Islamic education in the global and multicultural era. Keywords: